Drug resistance dependent on allostery: A P-loop rigor Eg5 mutant exhibits resistance to allosteric inhibition by STLC - Rose-Laure Indorato; Salvatore DeBonis; Isabel Garcia-Saez; Dimitrios A. Skoufias (Frontiers in Oncology, 2022)
The mitotic kinesin Eg5 has emerged as a potential anti-mitotic target for the purposes of cancer chemotherapy. Whether clinical resistance to these inhibitors can arise is unclear. We exploited HCT116 cancer cell line to select resistant clones to S-trityl-L-cysteine (STLC), an extensively studied Eg5 loop-L5 binding inhibitor. The STLC resistant clones differed in their resistance to other loop-L5 binding inhibitors but remained sensitive to the ATP class of competitive Eg5 specific inhibitors. Eg5 is still necessary for bipolar spindle formation in the resistant clones since the cells were sensitive to RNAi mediated depletion of Eg5. One clone expressing Eg5(T107N), a dominant point mutation in the P-loop of the ATP binding domain of the motor, appeared to be not only resistant but also dependent on the presence of STLC. Eg5(T107N) expression was associated also with resistance to the clinical relevant loop-L5 Eg5 inhibitors, Arry-520 and ispinesib. Ectopic expression of the Eg5(T107N) mutant in the absence of STLC was associated with strong non-exchangeable binding to microtubules causing them to bundle. Biochemical assays showed that in contrast to the wild type Eg5-STLC complex, the ATP binding site of the Eg5(T107N) is accessible for nucleotide exchange only when the inhibitor is present. We predict that resistance can be overcome by inhibitors that bind to other than the Eg5 loop-L5 binding site having different chemical scaffolds, and that allostery-dependent resistance to Eg5 inhibitors may also occur in cells and may have positive implications in chemotherapy since once diagnosed may be beneficial following cessation of the chemotherapeutic regimen.